Study of E-mail Data Services based on Delay Tolerant Network in The Riau Province Border Region - B. Kharisma, Oktaf; E. Laumal, Folkes; A. Cahyanto, Triawan; Ermayanti Susilo, Dwi; W. Sudarmadji, Petrisia (International Journal of Engineering and Technology, 2018)
Indonesia is an archipelagic country that is geographically unique, where most of the land has uneven land contours because it consists of mountains and valleys. This condition is one of the causes of the inequality of information dissemination even though the ICT infrastructure has supported and internet services are also available. Topographical factors and inequality of information dissemination pose digital deviations in the community, especially border areas in Riau Province which have not been able to enjoy internet services in some of the regions. Even though the process of data transmission to other regions is needed by both government agencies placed in border areas and the general public who need internet services for data transmission (text, audio, and video). Delay Tolerant Network (DTN) technology is a network protocol that allows communication networks to be applied in extreme environments that have long delay characteristics, high loss rates, and low connectivity levels. With DTN, internet services can be implemented and presented cheaply using only DTN Router which will move to areas that are not reachable by the internet and collect email data digitally. Furthermore, DTN Router and processes every transmission request from/to the border regions with extreme topography. By using the Flooding method applied to the DTN protocol, testing of e-mail data packet transmission from simulations at several locations in Riau is considered to have high data loss. Testing modeled by several computers with DTN, doing a bundle of data packages, transmitting to destinations and assessing the efficiency of their success. The test results show that the data transmission process in extreme areas using DTN protocol, Indicates that the larger the size of the file sent. So, the greater the time needed for data transmission. Approximate of time is needed of transmission data of the 95MB file that is 4,1 second..Â Â Â